PENGARUH PELATIHAN, KOMPENSASI DAN MOTIVASI TERHADAP KINERJA PENYULUH (Survei pada Dinas Pertanian dan Perikanan Kabupaten Ponorogo) - Noer, Novia Vrisnainila; Suddin, Alwi; Sriwidodo, Untung (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2020)
Government as public servant must prioritize public services. The research aims to analyze the significance of the effect of training, compensation and motivation on the performance of extension agents in the Department of Agriculture and Fisheries in Ponorogo Regency. The research population was 178 extension agents in the Department of Agriculture and Fisheries in Ponorogo Regency. The research sample is 30% and is taken by using a cluster proporsive random sampling technique to obtain a sample of 54 people. The data analysis technique of the research uses descriptive analysis, research instrument tests (validity and reliability tests), classic assumption test (multicollinearity test, autocorrelation test, heteroscedasticity test, normality test), multiple linear regression analysis, t test, F test, and coefficient of determination test. The results of the research show that training has no significant effect on the performance of extension agents in the Department of Agriculture and Fisheries in Ponorogo Regency, compensation has a significant effect on the performance of extension agents in the Department of Agriculture and Fisheries in Ponorogo Regency, and motivation has a significant effect on the performance of extension agents in the Department of Agriculture and Fisheries in Ponorogo Regency.